Penerapan Metode Multi-Objective Optimization By Ratio Analysis (MOORA) Pada Sistem Pendukung Keputusan Pemilihan Motor Bekas Terbaik ( Studi Kasus di Assalam Motor) - Sri Hariyati Fitriasih; Nur Rochman; Kumaratih Sandradewi; Bramasto Wiryawan Yudanto; Prihanto Prihanto (Journal of Information Technology, Computer Engineering and Artificial Intelligence (ITCEA), 2026)
Selecting a high-quality used motorcycle is complex because it involves multiple assessment criteria, including price, engine condition, year of manufacture, mileage, and completeness of the vehicle documents. At Assalam Motor, selecting the best used motorcycle remains a manual, subjective process that can lead to suboptimal decisions. Therefore, this study aims to develop a Decision Support System (DSS) to select the best motorcycle for use using the Multi-Objective Optimization by Ratio Analysis (MOORA) method. The MOORA method is used because it can handle multicriteria problems by effectively distinguishing between benefit and cost criteria. The developed system processes data on used motorcycles according to predetermined criteria and produces preference values to rank them. The study results indicate that the developed decision support system can provide recommendations on the best motorcycle to use in an objective, structured manner, thereby assisting Assalam Motor and consumers in making more precise, effective, and rational decisions.